Arsitektur Sistem Informasi Lembaga Sertifikasi (Studi Kasus Lembaga Sertifikasi Profesi Perbankan dan Sistem Pengendalian Online Sertifikasi Kompetensi pada Badan Nasional Sertifikasi Profesi) - Sarlawati Gita Avrianingsih - Perbanas Institute (Indonesian Journal of Networking and Security (IJNS), 2015)
Abstract –  Job competence certification in Indonesia set up by Badan Nasional Sertifikasi Profesi (BNSP) independent agency established under PP 23 of 2004 to regulate the labor competency certification in Indonesia. Banking Professional Certification was developed and implemented by Lembaga Sertifikasi Profesi Perbankan (LSPP) in order to create a strong banking industry and has a high competitiveness and resilient in the face of risk. To this direction, required, among others, work competency standards in order to create equality and increase the professionalism banker. In support of the vision and mission planning is necessary LSPP information systems architecture that defines the main activities and supporting activities as key business functions in the operations of the organization. Preparation of information systems architecture is done with TOGAF (The Open Group Architecture Framework) with eight components of architeture Development Method (ADM) consisting of: architecture vision, business architecture, information systems architecture, technology architecture, opportunities and solutions, migration planning, implementation governance , as well as change management architecture. By planning the architecture of integrated information systems to meet the needs of performance improvement of business processes in information systems professional certification in Indonesia. Abstrak –  Sertifikasi kompetensi kerja di Indonesia diatur Badan Nasional Sertifikasi Profesi (BNSP) lembaga independen yang dibentuk berdasarkan PP No. 23 Tahun 2004 untuk mengatur sertifikasi kompetensi kerja di Indonesia. Sertifikasi Profesi Perbankan dikembangkan dan dilaksanakan oleh Lembaga Sertifikasi Profesi Perbankan  (LSPP) guna menciptakan industri perbankan yang kuat dan memiliki daya saing yang tinggi serta memiliki ketahanan dalam menghadapi risiko. Untuk ke arah tersebut, diperlukan antara lain, standar baku kompetensi kerja agar tercipta kesetaraan dan peningkatan profesionalitas bankir. Dalam mendukung visi dan misi LSPP diperlukan perencanaan arsitektur sistem informasi yang dapat mendefinisikan aktifitas utama dan aktifitas pendukung sebagai fungsi bisnis utama dalam operasional organisasi. Penyusunan arsitektur sistem informasi dilakukan dengan TOGAF (The Open Group Architecture Framework) dengan delapan komponen dari Architeture Development Method (ADM) yang terdiri dari : architecture vision, business architecture,information system architecture, technology architecture, opportunities and solution, migration planning, implementation governance, serta architecture change management. Dengan melakukan perencanaan arisitektur sistem informasi yang terintegrasi dapat memenuhi kebutuhan peningkatan kinerja proses bisnis dalam sistem informasi sertifikasi profesi di Indonesia.Kata kunci:  Arsitektur Sistem Informasi, TOGAF, ADM, BNSP, LSPP